ANALISIS FAKTOR YANG MEMENGARUHI MINAT BERWIRAUSAHA PADA MAHASISWA KEPERAWATAN DI STIKES GUNUNG SARI - Nur Ain Ar Bague; Abubakar Betan; Abdul Malik Azikin; Normalia; Hijrah (Jurnal Kesehatan, 2026)
Background: Limited job availability for higher education graduates necessitates the strengthening of the entrepreneurship sector, including in nursing. Nursing students hold strategic potential to initiate healthcare innovations through the nursepreneur concept, yet their interest is influenced by various internal and external factors that require in-depth understanding. Objective: This study aims to analyze the influence of attitude, family support, motivation, and knowledge level on entrepreneurial interest among nursing students at STIKES Gunung Sari. Methods: This quantitative study with a cross-sectional design involved 56 respondents selected via total sampling. Data were collected using structured questionnaires and statistically analyzed using the chi-square test at a significance level of α=0.05. Results: Findings indicate that personal attitude (p<0.05) and family support (p<0.05) have a significant correlation with high entrepreneurial interest. Conversely, motivation and knowledge level did not show a significant influence in this study. Conclusion: Positive attitudes and supportive family environments are the primary determinants shaping students' entrepreneurial intensity. Educational institutions are encouraged to practically integrate entrepreneurial values into  the curriculum and involve families to build a supportive ecosystem for graduates' economic independence.